Supplementation of Mixed Organic Acids Improves Growth Performance, Meat Quality, Gut Morphology and Volatile Fatty Acids of Broiler Chicken - Jiayu Ma (MDPI AG, 2021)
Background: Organic acid as a green feed additive is increasingly favoured by enterprises and scholars, but little emphasis has been placed on the effect of organic acids on broiler meat quality. Methods: A total of 192 male chicks (one-day-old, weighted 48.40 ± 0.64 g) were selected to investigate the effect of mixed organic acids (MOA) on growth performance, meat quality as well as fatty acids profile. Chicks were randomly allocated to three treatments with eight replicates and eight chicks per replicate, including a corn–soybean basal diet with 0 (CON), 3000 mg/kg (low MOA; LMOA), and 6000 mg/kg (high MOA; HMOA) MOA. The experiment was divided into starter (d 1–d 21) and grower (d 22–d 42) phases. Results: Broilers supplemented with LMOA and HMOA enhanced (p < 0.05) the final body weight and average daily gain in the grower and overall phases. An improved (p < 0.05) feed conversion ratio in the grower and overall phases was observed in broilers supplemented with LMOA. The breast and thigh muscles pH24h were higher (p < 0.05) in broilers fed with HMOA and the redness in thigh meat was also improved (p < 0.05). Additionally, supplementing LMOA increased (p < 0.05) the saturated fatty acids, unsaturated fatty acids and the ratio of polyunsaturated fatty acids to saturated fatty acids in breast meat. A positive effect occurred (p < 0.05) on jejunal villus height and ileal crypt depth in 21 d broilers supplemented with HMOA. Conclusion: Our findings indicated that dietary supplementation of MOA could improve the growth performance, meat quality, and fatty acids profile, as well as intestinal morphology. Furthermore, diets supplemented with mixed organic acids at 3000 mg/kg may be more desirable, considering the overall experimental results in broilers.